Generational Leadership: Exploring Intergenerational Dynamics and Leveraging HR Practices to Foster Effective Leadership, Productivity, and Team Collaboration - Malcolm, Giovanni (Global journal of Business and Integral Security, 2024)
The utility industry faces significant leadership challenges due to demographic shifts and the changing expectations of a multi-generational workforce. As Baby Boomers remain in the workplace and younger generations assume leadership roles, understanding generational differences in leadership styles becomes crucial. This doctoral thesis explores how human resource practitioners assist leaders in the utility industry by identifying factors that contribute to effective multi-generational leadership. Studies indicate that leaders struggle to manage the diverse generational workforce. Issues such as misconceptions, communication barriers, and high employee turnover have compelled HR practitioners to rethink strategies. Existing literature lacks focus on generational leadership in utility companies in developing countries like Jamaica, leading to a deficiency in effective leadership practices. This study employed a qualitative research design, including face-to-face interviews with business executives and HR practitioners, focus groups with different age groups, and observation techniques, involving 30 participants. Thematic analysis was used to interpret the data. Key findings reveal that misconceptions, miscommunication, and unconscious biases significantly hinder productivity and team collaboration in a multi-generational workforce. Leaders’ ineffectiveness in addressing these issues exacerbates the negative impacts. The research underscores the need for HR practitioners to better equip leaders to manage a multi-generational workforce. The study provides strategies to enhance leadership capacity, improve communication methods, and address demographic differences. It also highlights the correlation between generational diversity and organizational performance, offering recommendations for building capacity and competence. This paper contributes to the body of knowledge on how HR practitioners can help leaders in Jamaica's utility industry understand and effectively lead a multi-generational workforce. By improving communication and individualizing leadership approaches, leaders can increase productivity, enhance team collaboration, and improve retention. The findings advocate for judicious business practices, enabling utility companies to address generational differences holistically, thus fostering a more productive and collaborative work environment.